AB0747 Early and Sustained Modified PSARC Response in Psoriatic Arthritis Patients Treated with Ustekinumab: Results from PSUMMIT 1 and PSUMMIT 2. (10th June 2014) - McInnes, I.; Ritchlin, C.; Rahman, P.; Puig, L.; Gottlieb, A.B.; Song, M.; Randazzo, B.; Li, S.; Wang, Y.; Mendelsohn, A.; Kavanaugh, A.
Abstract : Background: We have previously reported the efficacy and safety results of ustkeinumab (UST), an IL-12/23 p40 inhibitor, in patients with active psoriatic arthritis up to two years of UST treatment from the PSUMMIT 1 and PSUMMIT 2 trials. Objectives: Here, we further describe the sustained effects of UST using the modified Psoriatic Arthritis Response Criteria (PsARC) response. Although not validated, the PsARC has been widely used in psoriatic arthritis clinical trials. Methods: Adult PsA patients with active disease (≥5 SJC and ≥5 TJC; CRP≥0.3mg/dL [ULN 1.0 mg/dL]) despite DMARD and/or NSAID therapy (PSUMMIT 1, n=615; PSUMMIT 2, n=312 [of which 180 pts were previously treated with DMARD and/or NSAID, and prior anti-TNFα therapy]) were randomized to UST45mg, 90mg, or PBO at wks 0, 4, and q12wks, thereafter. PBO-treated pts were crossed over to UST45mg at wks24 and 28 followed by q12wk dosing. At wk16, patients with <5% improvement in TJC & SJC entered blinded early escape [EE] (PBO→ UST45mg; UST45mg→ 90mg; 90mg→ 90mg). No concomitant DMARDs with the exception of MTX (approximately 50% of patients in each study) were permitted. Patients were considered a responder using the modified PsARC if improvement was demonstrated in at least 2 (including at least 1 of the joint criteria) of the following criteria and no deterioration was noted in the other criteria: ≥30% decrease in the swollen joint count, ≥30% decrease in the tender joint count, ≥20% improvement in the patient's overall assessment (VAS), and ≥20% improvement in the physician's overall assessment (VAS). Proportions of patients with PSARC response were assessed at wks 4, 8, 12, 24, 28, 40, and 52. Results: PSARC results are summarized in Table 1 . Statistically significantly higher PSARC response rates were observed as early as wk4 for both UST groups compared to PBO in the PSUMMIT 1 trial and statistically significantly higher responses were also observed at wks 8, 12 and 24 for both UST dose groups compared to PBO in both trials. Responses in both UST dose groups continued to increase after wk24, reached a plateau at wk 28 and were maintained through wk52. Patients who were initially randomized to PBO and crossed over to 45mg achieved similar responses to those originally randomized to UST. Higher PSARC responses were consistently observed at wk8-24 for both UST groups compared with the placebo group regardless of baseline MTX status. The early onset of PSARC responses observed was consistent with early onset of ACR 20 responses. UST was generally well-tolerated. Conclusions: Significantly higher PSARC responses were observed as early as wk4-8 for both UST dose groups compared with PBO. Improvements observed at wk24 continued to increase at wk28 and were sustained through wk52. Disclosure of Interest: I. McInnes Grant/research support: Janssen R & D, LLC, C. Ritchlin Grant/research support: Janssen R & D, LLC, P. Rahman Grant/research support: Janssen R & D, LLC, L. Puig Grant/research support: Janssen R & D, LLC, A. Gottlieb Grant/research support: Janssen R & D, LLC, M. Song Employee of: Janssen R & D, LLC, B. Randazzo Employee of: Janssen R & D, LLC, S. Li Employee of: Janssen R & D, LLC, Y. Wang Employee of: Janssen R & D, LLC, A. Mendelsohn Employee of: Janssen R & D, LLC, A. Kavanaugh Grant/research support: Janssen R & D, LLC DOI: 10.1136/annrheumdis-2014-eular.3944